Identification of Domestic Liquid Waste Sanitation Conditions in an Effort the Improvement of Sanitation in Karanganyar - Indrastuti, Nining; Ashadi, Ashadi; Setyono, Prabang; Sunarto, Sunarto (Proceeding International Conference on Science and Engineering, 2019)
Domestic liquid waste sanitation conditions in Karanganyar is the circumstances or description of the environment sewage from household activity results in particular black water located in Karanganyar. Identification purposes is to provide information about the condition of domestic waste sanitation in Karanganyar, which is necessary to address insecurity about sanitation. Karanganyar is a Regency which have abundant areas prone to sanitation. Karanganyar has 177 villages with poor sanitation conditions following six villages at risk is very high, 77 Villages at high risk, medium risk and the village of 54 40 Villages are less risky. Sanitary conditions are influenced by various factors, among others, the type of means of sanitation and the quantity of domestic waste generated per person in district at Karanganyar. Type of sanitation facility that is in the community's variegated Karanganyar Regency such as cubluk, jumbleng, septic latrines with goose neck and WC sit with septic tanks. Socio-economic conditions determine the type of selected community sanitation. According to the BPS, the number of poor households in Karanganyar of 5 rating is the largest Sub Gondangrejo, Mojogedang, Jumapolo, Kebakkramat and Karanganyar. From the results of the sample population of 285 quisioner the respondent inhabitants in Karanganyar earned a percentage of population in a town is not served by sanitation more than 60% as follows Jenawi 94.1%, Karangpandan 78%, Jumapolo 75.1%, Karanganyar 70.8%, Jatiyoso 70%, Mojogedang 65.4%, Jumantono 63%, Kebakkramat 62.5% dan Ngargoyoso 61.2%. The results of the identification that Kecamatan prone concluded that sanitation, thus requiring handling domestic waste processing to improve sanitation in Karanganyar Regency. The selected processing system and is expected to effectively, efficiently and in accordance with the socio-economic conditions of society as well as the sustainable.